Родина, Родина, ты - это мы!: Очерки истории пионер. орг. Удмуртии / Т. П. Костицына - Костицына Татьяна Павловна (Удмуртия, 1980)
Экземпляры: ф-10 (ретроконверсия) / Инвентарный номер: 858 / Цена: 1.10 / Сис.шифр: 63.3 / Авт.знак: К 72 / ГРНТИ: 03 / ББК: 63.3